Evolution of Disney Princesses and Its Impacts on Gender Roles and the Portrayal of Love Among Young Girls - Sun JiaYu (SHS Web of Conferences, 2023)
The three waves of feminism had an impact on how Disney princesses were portrayed. Since the 1950s, women have been portrayed as Disney princesses in the quest for gender equality and the reversal of traditional gender norms. This paper is based on a literature review. The paper would analysis the image of Disney princesses in three major eras, and refine the female characters shown in each film to study the different stages presented by Disney princesses, which further presents the impacts on gender roles and the portrayal of love. From the Classic princess, to the awakening of female consciousness, and eventually becoming an independent and brave queen, Disney princesses have undergone three metamorphoses. Women and men started to achieve equal roles, the gender roles switched from women working at home to women starting to pursue their careers. For Disney princesses, they are no longer obsessed with the pursuit of love and marriage, they begin to have more ways to achieve self-actualization.